Biopharmaceutical classification system: A strategic tool for oral drug delivery technology - Sachan, Nikhil K; Bhattacharya, A; Pushkar, Seema; Mishra, A (Asian Journal of Pharmaceutics (AJP), 2014)
The biopharmaceutical classification system (BCS) is a new concept in the field of pharmaceutical science and technology. This is a valuable tool for the formulation scientists, for the selection and design of the formulation of any drug substance. The recent developments have also enabled us to predict the solubility and permeability characteristics of the drug molecule in the early development stages so that the necessary structural changes can be made to the molecule in order to optimize the pharmacokinetic parameters.The BCS has also got a place in various guidance documents of regulatory mportance. This article reviews the criteria for classifying drugs according to the BCS and discusses further potential applications of the BCS, including the developments of new drugs and controlled release products.